Nietzsche: as paixões como afirmação da vida e construção de uma nova ética - Sousa, Érica Costa (2013)
The present dissertation – entiteld Nietzsche: the passions as life affirmation e constructing of a “new ethics” – aims at thinking of a “new ethics” in Nietzsche’s philosophy, based upon his early writtings as well as on his lattest works. While developing this theme, we intend to consider, in a first moment, the notion of body as guide line and background of the analysis - taking it not as a dualistic opposition to the soul, but as a multiplicity of forces within an ethernal becoming, contributing towards a formation and transformation of living; then, after having considered the question of the inversion of Platonism, in line with the ideia of creation and yes-saying to life, we finally hope to point out a possible “new ethics” in Nietzsche’s philosophy.